1984
DOI: 10.1128/jcm.19.2.301-302.1984
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Autobac IDX system for rapid identification of Enterobacteriaceae and nonfermentative gram-negative bacilli

Abstract: The Autobac IDX system was evaluated for its ability to accurately identify 290 gram-negative bacilli from 18 different genera. Excluding isolates with a low identification probability, the overall sensitivity of the system was found to be 95.8%. Late lactose-fermenting Escherichia coli, Citrobacter freundii, and Proteus mirabilis accounted for over 90% of the misidentifications. The Autobac IDX system offers a rapid and reliable method for the identification of gram-negative bacilli. An increased emphasis has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
2

Year Published

1985
1985
1992
1992

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 6 publications
0
11
0
2
Order By: Relevance
“…Although the conventional macrotube methods of bacterial identification are still used in microbiology laboratories, the state of the art is the systems approach to identification with emphasis on standardization, speed, reproducibility, and in the last several years, mechanization and automation (1,3,4,(6)(7)(8)(14)(15)(16)(17). Thus, the conventional methods have been adapted or streamlined into miniaturized test systems which use numerical coding systems, computer-generated data bases, and reaction endpoints which can be reached after 4 to 6 h of incubation (1, 3, 4, 6-8, [14][15][16][17].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the conventional macrotube methods of bacterial identification are still used in microbiology laboratories, the state of the art is the systems approach to identification with emphasis on standardization, speed, reproducibility, and in the last several years, mechanization and automation (1,3,4,(6)(7)(8)(14)(15)(16)(17). Thus, the conventional methods have been adapted or streamlined into miniaturized test systems which use numerical coding systems, computer-generated data bases, and reaction endpoints which can be reached after 4 to 6 h of incubation (1, 3, 4, 6-8, [14][15][16][17].…”
mentioning
confidence: 99%
“…Several of the commercial systems currently available are potentially subject to reader bias despite offering a variety of biochemical tests, systematic coding systems, and broad computer-generated data bases (7). Fortunately, this problem has largely been circumvented with the development of microprocessor-based instrumentation which can both read and interpret tests in an identification system, thus providing excellent standardization, accuracy, and reproducibility (4,6,7,(14)(15)(16)(17)(18)24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Shulman et al (105) reported on the ability of the ALA-DIN to read UniScept 20E panels. A total of 300 isolates (144 E. coli, 45 Proteus/Providencia spp., 27 KiebsiellalEnterobacter spp., 18 Serratia spp., 12 Pseudomonas spp., and 54 other organisms) were tested. On a test-for-test basis, the ALADIN and visual readings of 300 organisms showed a 99.0% level of correlation.…”
Section: Aladin and Autoreadermentioning
confidence: 99%
“…In summary, early studies with the Autobac Series II demonstrated that most of the gram-negative bacilli commonly isolated in the clinical laboratory were correctly identified (10,11,18,27,60,106,111). However, problems were reported in the identification of such organisms as Enterobacter cloacae, C. freundii, Proteus vulgaris, Providencia spp., Salmonella spp., Shigella spp., P. cepacia, and many uncommon organisms.…”
Section: Introductionmentioning
confidence: 99%